Utilization of Gravimetric Satellite Data for Delineating of Subsurface Model of The Purwokerto-Purbalingga Groundwater Basin - Sehah Sehah; Urip Nurwijayanto Prabowo; Sukmaji Anom Raharjo; Laila Ariska (Faculty of Geography, Universitas Gadjah Mada, 2022)
The utilization of gravimetric satellite data has been carried out to delineate the subsurface model of the Purwokerto-Purbalingga Groundwater Basin. Access and processing of satellite gravity anomalies data were carried out to obtain the residual gravity anomalies data. Modeling of the residual gravity anomalies data was conducted along the AA′, BB′, and CC′ trajectories. The modeling results show a basin model filled by alluvial deposits (1.75 g/cm3 and 2.28 g/cm3) with a maximum depth of about 402 m for the AA′ trajectory, 543 m for the BB′ trajectory, and 463 m for the CC′ trajectory. The modeling results show that this alluvial basin is delimited by impermeable and semi-impermeable layers, which include laharic deposits of Slamet Volcano (2.61 g/cm3), andesite lava deposits (2.90 g/cm3), Tapak formation rocks (2.50 g/cm3), breccia rocks of Tapak formation (2.70 g/cm3), and breccia rocks of Halang formation (2.80 g/cm3). The fairly large thickness of alluvial deposits supported by dug-well water tables data and resistivity data indicates that the potential of groundwater in the Purwokerto-Purbalingga Groundwater Basin area is very large. The results of the study are expected to be a solution to overcome droughts that often occur in the Banyumas and Purbalingga regencies, as well as for the development of groundwater-based irrigation.